Triptolide suppresses IL-1β-induced expression of interleukin-8 by inhibiting ROS-Mediated ERK, AP-1, and NF-κB molecules in human gastric cancer AGS cells - Li, Shinan; Sah, Dhiraj Kumar; Arjunan, Archana; Ameer, Mohamed Yazeer; Lee, Bora; Jung, Young-Do (Frontiers in Oncology, 2025)
Triptolide, the major component of Chinese herbal medicine Tripterygium wilfordii Hook F, possesses potent anticancer and anti-inflammatory effects. IL-8, a proinflammatory cytokine, is associated with cancer cell proliferation and angiogenesis. Here, we found that Triptolide has an inhibitory effect on IL-1β-induced IL-8 expression in human gastric cancer cells, via the suppression of reactive oxygen species (ROS) production, AP-1, and NF-κB activation, which in turn affects human endothelial cell angiogenetic activity in tumor microenvironments. Human gastric AGS cells were treated with IL-1β (10 ng/mL) and Triptolide (0–20 nM), and the ROS generation, ERK, AP-1, and NF-κB signaling were all investigated. These results demonstrate that Triptolide inhibits the IL-1β-induced IL-8 expression in gastric cancer cells by inhibiting ROS production and angiogenesis, via the dose-dependent attenuation of ERK, AP-1, and NF-κB activation. In this study, we showed that Triptolid inhibits ROS/ERK-mediated AP-1 and ROS-mediated NF-κB axes potentially leading to an improved treatment outcome for gastric cancer and its associated tumor microenvironment.